PEMBERDAYAAN PELAKU UMKM MELALUI PELATIHAN DIGITAL MARKETING - Hanafi, Rustam; Sutapa; Mulyana (Fakultas Ekonomi dan Bisnis Islam, 2025)
This community empowerment study aims to enhance the digital marketing capabilities of Micro, Small, and Medium Enterprises (MSMEs) in Pringrejo Village, West Pekalongan District, Pekalongan City. The rapid growth of digital technology and shifts in consumer behavior toward online shopping require MSMEs to adapt and build digital readiness. This program applies a community-empowerment methodology that integrates tutorial sessions, hands-on practice, and live-streaming simulations across multiple e-commerce and social media platforms. In addition, the program adopts Community-Based Research (CBR), Participatory Action Research (PAR), Asset-Based Community Development (ABCD), and Service Learning (SL) to ensure participatory engagement, local asset mobilization, and sustainable learning outcomes. A retrospective post-test survey was administered to evaluate changes in participants’ knowledge and skills before and after the training. The results indicate that 80% of participants had never attended similar training, highlighting a digital literacy gap. Post-training evaluations showed a significant improvement in participants’ understanding, with an average score of 4.35 on a 5-point scale, and 96% of participants reported comprehension of the material. These findings demonstrate that the participatory digital marketing training model effectively improves MSMEs’ digital competencies and supports market expansion through e-commerce channels. The program contributes to strengthening MSMEs’ resilience and competitiveness in the digital era while offering a replicable empowerment model for other rural business communities.